0478 Inhalation and dermal exposure to toluene among printing workers in a plastic bag factory. (21st August 2017) - Phanprasit, Wantanee; Songpek, Kanchanok; Boonyayothin, Vorakamol; Sujirarat, Dusit
Abstract : Introduction: The study was conducted in a plastic bag factory to explore the inhalation and dermal exposure to toluene of the printing workers who wore no PPE and the potential of a charcoal cloth pad (CCP) as a dermal sampler to assess the skin permeation of liquid toluene. Methods: Twenty-seven stationary air samples were collected on the same 9 days with the urine and dermal samples from 11 printing workers. The CCPs were wrapped on each of the workers' fingers. Air samples were collected and analysed according to NIOSH # 1501 and 65 post-shift urine samples were collected and analysed for toluene using GC-HS/FID. Multiple linear regression was employed to analyse the association of the variables. Result: T three urine samples contained toluene exceeding the BEI of 30 mg/L. Toluene on the CCP (TolCCP) is a meaningful predictor for the UTol (p-value=0.027), with r and r 2 of 0.441 and 0.195 respectively. The absorbed dose of toluene determined from TolCCP ranging in between 1.05–91.94 mg and counting for the maximum of 12.3% TLV. Discussion: The mean of TWA was above the TLV while that of the UTol was well below the BEI. This indicated that the TWA concentrations could be overestimated due to the size of the room and good general ventilation. The dermal exposure was not significant if the workers wear respirators, but if not the dermal absorption could contribute to the overall uptake and may cause the exposure above the TLV.